The Chrysanthemums TV Show Still - Mac and Ava Productions; CBS Film Sales Inc.:::Creator::::::::::::
Nina Capriola kneeling in garden speaking with Paul Henri in 'The Chrysanthemums' episode of the 1960's 'The Robert Herridge Theater' television show.